The Efficacy of Pharmacological and Non-Pharmacological Therapy In Thyroid Storm Patients With Cardiovascular Complications : Literature review - Nur Rezky Rutami Amir; Yulistiani Yulistiani (Universitas Malahayati Lampung, 2025)
ABSTRACT Tyroid storm is a life-threatening with clinical manifestation of thyrotoxicosis can cause other organ dysfuntion such as cardiovascular disorders. Therefore, eary detection using Burch and Wartofsky Point Scale that treatment can be optimally. The purpose of literature review is examine the treatment used thyroid storm with cardiovascular complications and the effectiveness of therapy achieve eutiroid. The research use a qualitative method with a literature review design. Data collected from article, journal using keywords and based on inclusion criteria been used Google Scholar and Science Direct databases. The results of journal screening is five journal with case report design. Pharmacological treatment use thionamides, beta blockers, corticosteroids, and potassium iodide, The efficacy of therapy depending on the patients complications. Non-Pharmacological therapy plasmapheresis, is used if the patient is given pharmacological therapy and does not show a response after 48 hours of administration. The efficacy of plasmapheresis shows improved clinical effect and euthyroid state. Keywords: Thyroid storm, Pharmacological, Non-Pharmacological, Eutiroid